Perancangan Desain UI/UX Aplikasi Candi BumiAyu Sebagai Media Promosi - Sartika; Anung Rachman; Ipung Kurniawan Yunianto (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2023)
With the development of technology, a tourist spot can now not only be visited in person but also virtually. In addition, technology can also be used as an effective and creative medium for product promotion. The most visible technology is gadgets. A gadget certainly requires an application or software in it. Based on the results of observations, the community still does not know and understand the tourist attractions of the Bumiayu Temple which is located in Penukal Abab Lematang Ilir, South Sumatra. Thus, this design aims to develop and design the UI/UX design for the Bumiayu Temple Application as a medium that can be applied to the Bumiayu Temple. This research uses a human-centered or human-centric design approach to solve problems and present innovations, namely Design Thinking. Design thinking is carried out through 5 stages, namely empathize, define, ideate, prototype, and test. This research will develop or design a smartphone application-based promotion of the Bumiayu Temple Cultural Heritage. Through the development of a smartphone application-based promotion system for the Cultural Heritage of the Bumiayu Temple, it is hoped that it can provide information to the public who are curious about the Bumiayu Temple.